2018
DOI: 10.3390/pharmaceutics10040274
|View full text |Cite
|
Sign up to set email alerts
|

SPC Liposomes as Possible Delivery Systems for Improving Bioavailability of the Natural Sesquiterpene β-Caryophyllene: Lamellarity and Drug-Loading as Key Features for a Rational Drug Delivery Design

Abstract: The natural sesquiterpene β-caryophyllene (CRY) has been highlighted to possess interesting pharmacological potentials, particularly due to its chemopreventive and analgesic properties. However, the poor solubility of this sesquiterpene in aqueous fluids can hinder its uptake into cells, resulting in inconstant responses of biological systems, thus limiting its application. Therefore, identifying a suitable pharmaceutical form for increasing CRY bioavailability represents an important requirement for exploitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Indeed, β-caryophyllene is known to be a lipophilic molecule with very low water solubility and to possess a great capacity to interact with membrane phospholipids and to be partitioned in the lipid bilayer, altering the cooperativity between phospholipids and between phospholipids and transporter proteins, thus likely affecting their function [75]. Recently, this hypothesis has been confirmed in a membrane model of soybean phosphatidylcholine, in which β-caryophyllene, at high concentrations, was found to be retained and embedded in the liposome bilayer, likely due to a stable interaction with the phospholipid: this effect was similar to that induced by cholesterol, known to alter membrane packing, order, and fluidity [55].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, β-caryophyllene is known to be a lipophilic molecule with very low water solubility and to possess a great capacity to interact with membrane phospholipids and to be partitioned in the lipid bilayer, altering the cooperativity between phospholipids and between phospholipids and transporter proteins, thus likely affecting their function [75]. Recently, this hypothesis has been confirmed in a membrane model of soybean phosphatidylcholine, in which β-caryophyllene, at high concentrations, was found to be retained and embedded in the liposome bilayer, likely due to a stable interaction with the phospholipid: this effect was similar to that induced by cholesterol, known to alter membrane packing, order, and fluidity [55].…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, β-caryophyllene is known to bind to the CB2 receptor as an agonist and to induce anti-inflammatory, analgesic and neuroprotective effects [46][47][48]. Furthermore, both sesquiterpenes have been highlighted to possess interesting chemopreventing properties, due to their ability to counteract cell injury induced by environmental pollutants [49][50][51][52] and to inhibit cancer cell growth and proliferation, through affecting several key pathways for cancer development, such as mitogen-activated protein kinase (MAPK), PI3K/AKT/mTOR/S6K1 and STAT3 pathways [47,[53][54][55][56]. Also, they were reported to potentiate the efficacy of some anticancer drugs, acting as chemosensitizers [15][16][17]19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al [ 153 ] found that β-caryophyllene was the major bioactive constituent of the essential oil from Chrysanthemum boreale and produced cytotoxic effects in A549 and NCI-H358 cells. We have also reported that the triple negative MDA-MB-468 breast cancer cells were about 2-fold more sensitive to β-caryophyllene cytotoxicity than HepG2 cells [ 242 ].…”
Section: Caryophyllane Sesquiterpenes In Cancer Chemopreventionmentioning
confidence: 99%
“…Indeed, we have found that administering liposomal formulations of β-caryophyllene in triple negative MDA-MB-468 breast cancer cells, the cytotoxic power of the sesquiterpene was increased (up to 4-fold) significantly [ 242 ]. Di Sotto et al [ 242 ] also highlighted that the lipid-to-drug ratio should be considered as a critical parameter for enabling β-caryophyllene release from a lipid-based nanocarrier, in order to avoid the substance condensing effect on the bilayer, and for increasing its cytotoxic power in cancer cells.…”
Section: Caryophyllane Sesquiterpenes In Cancer Chemopreventionmentioning
confidence: 99%
See 1 more Smart Citation